Perspective insights into hydrogels and nanomaterials for ischemic stroke - Yu, Qingbo; Jian, Zhang; Yang, Dan; Zhu, Tao (Frontiers in Cellular Neuroscience, 2023)
Ischemic stroke (IS) is a neurological disorder prevalent worldwide with a high disability and mortality rate. In the clinic setting, tissue plasminogen activator (tPA) and thrombectomy could restore blood flow of the occlusion region and improve the outcomes of IS patients; however, these therapies are restricted by a narrow time window. Although several preclinical trials have revealed the molecular and cellular mechanisms underlying infarct lesions, the translatability of most findings is unsatisfactory, which contributes to the emergence of new biomaterials, such as hydrogels and nanomaterials, for the treatment of IS. Biomaterials function as structural scaffolds or are combined with other compounds to release therapeutic drugs. Biomaterial-mediated drug delivery approaches could optimize the therapeutic effects based on their brain-targeting property, biocompatibility, and functionality. This review summarizes the advances in biomaterials in the last several years, aiming to discuss the therapeutic potential of new biomaterials from the bench to bedside. The promising prospects of new biomaterials indicate the possibility of an organic combination between materialogy and medicine, which is a novel field under exploration.